ANALISIS SISTEM INFORMASI KOPERASI SIMPAN PINJAM MENGGUNAKAN METODE WEIGHTED PRODUCT - Armiati, Sari; Hasanudin, Kiki; Yulientinah, Dewi Selviani; Mulyanti, Khairaningrum; Choldun R, Muhammad Ibnu (Universitas Logistik dan Bisnis Internasional, 2025)
In the rapidly developing digital era, information systems have become crucial in improving organizational efficiency and productivity. In XYZ Cooperative, information systems also play an important role. This cooperative, which is under a government agency, has a vision to improve the welfare of its employees through savings and loan services. However, in performing its business processes, this cooperative has not had applications and digital data storage, so there is a lot of work that is conducted redundantly. The aim of the research is to develop a cooperative information system (SIKOP) using the Weighted Product method. This research explains the analysis phase. The Weighted Product method is used to calculate the eligibility of an employee when applying for a loan at the cooperative, using 5 criteria. As a case study, the calculation was carried out on 20 current cooperative members. In the analysis phase, business processes were defined by using Porter Diagrams. The details of main activities were described by using Business Process Management Notation (BPMN). Software user requirements for application design features were measured by using the Kano method by distributing questionnaires to 30 respondents. The results of measuring software user requirements are the feature categories: 8 one-dimensional features, 3 must-be features and 3 indifferent features. The outputs of the research phase of the analysis of the savings and credit cooperative information system are software analysis documents and publication as knowledge dissemination and a basis for the next research phase.